Technology ease of use and adoption for open and distance learning: challenges from rural Nigerian communities (2025)
Perceived ease of use is a critical determinant of technology adoption and effective utilization, particularly in educational contexts. While previous studies have primarily linked ease of use to factors such as system design, training, and user support, the influence of technology availability, accessibility, individual differences, and geographic location has received comparatively little attention. This study examined the perceived availability, accessibility, and ease of use of technology among Open and Distance Learning (ODL) students residing in rural communities across Nigeria. Using a mixed-methods approach, data were collected from 453 students through a structured questionnaire designed to measure their perceptions of technology-related variables. Descriptive statistics, including frequency distributions, means, and percentages, were employed for data analysis. The findings indicated that ODL technologies were generally perceived as available (mean = 3.31 > 3.0), accessible (mean = 3.12 > 3.0), and relatively easy to use (mean = 3.03 > 3.0). However, students reported several challenges that hindered effective technology utilization, such as erratic power supply, poor internet connectivity, high data costs, and financial constraints. These infrastructural, economic, and skills-related barriers were found to significantly limit both access to and effective use of ODL technologies. The study concludes that improving technology availability and usability requires targeted investment in digital infrastructure, affordable connectivity, and continuous digital literacy training. It further recommends that ODL platforms be designed with user-centered principles to promote inclusivity and ensure equitable access to higher education opportunities for learners in underserved rural communities